An optimized g-tensor for Rhodobacter capsulatus cytochrome c2 in solution: a structural comparison of the reduced and oxidized states. - Zhao, D. (Cold Spring Harbor Laboratory Press, 1996)
The optimized g-tensor parameters for the oxidized form of Rhodobacter capsulatus cytochrome c2 in solution were obtained using a set (50) of backbone amide protons. Dipolar shifts for more than 500 individual protons of R. capsulatus cytochrome c2 have been calculated by using the optimized g-tensor and the X-ray crystallographic coordinates of the reduced form of R. capsulatus cytochrome c2. The calculated results for dipolar shifts are compared with the observed paramagnetic shifts. The calculated and the observed data are in good agreement throughout the entire protein, but there are significant differences between calculated and experimental results localized to the regions in the immediate vicinity of the heme ligand and the region of the front crevice of the protein (residues 44-50, 53-57, and 61-68). The results not only indicate that the overall solution structures are very similar in both the reduced and oxidized states, but that these structures in solution are similar to the crystal structure. However, there are small structural changes near the heme and the rearrangement of certain residues that result in changes in their hydrogen bonding concomitant with the change in the oxidation states; this was also evident in the data for the NH exchange rate measurements for R. capsulatus cytochrome c2.